1993
DOI: 10.1007/bf01277026
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of long term dopamine D2 receptor blockade after depot neuroleptics

Abstract: Two patients with extrapyramidal side effects after the use of fluphenazine decanoate were evaluated by means of IBZM-SPECT. Dopamine D2 receptor occupancy 1.5 months after withdrawal still amounted to 83% and 50%. More attention should be focused on long term effects of neuroleptics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…This Þnding conÞrmed previously reported long term D 2 receptor blockade for up to 7 weeks after depot neuroleptics (Baron et al 1989;Harasko-van der Meer et al 1993). The second SPECT study in case 2 was probably not inßuenced by the pretreatment with depot neuroleptics, because it was performed more than 15 weeks after the last depot injection.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This Þnding conÞrmed previously reported long term D 2 receptor blockade for up to 7 weeks after depot neuroleptics (Baron et al 1989;Harasko-van der Meer et al 1993). The second SPECT study in case 2 was probably not inßuenced by the pretreatment with depot neuroleptics, because it was performed more than 15 weeks after the last depot injection.…”
Section: Discussionsupporting
confidence: 87%
“…Carry-over e¤ects of prior treatment with oral antipsychotics were thought to be negligible after 2 weeks (Baron et al 1989). Not surprisingly, PET (Baron et al 1989) and SPECT (Harasko-van der Meer et al 1993) investigations revealed that injectable depot neuroleptics blocked D 2 receptors for considerably longer.…”
Section: Introductionmentioning
confidence: 96%
“…One of the most important confounding variable is premedication with typical neuroleptics and speciÞcally with depot formulations. As already previously shown, pretreatment with depot-neuroleptics with a pause for as long as 3 months is associated with higher striatal D 2 receptor occupancy rates (Harasko-van der Meer et al 1993;Tauscher et al 1997). We were also able to detect this phenomenon during sertindole treatment in two of our patients who were pretreated with depot medication.…”
Section: Discussionsupporting
confidence: 64%
“…In the PET examination of a single patient, Farde and colleagues (23) found that after withdrawal of oral haloperidol for up to 54 hours, there was a rapid fall in serum drug levels without a significant reduction in D 2 receptor occupancy. Withdrawal of depot preparations of fluphenazine decanoate (24) and haloperidol decanoate (25) resulted in high D 2 dopamine receptor occupancy for several months.…”
Section: Discussionmentioning
confidence: 99%